1986
DOI: 10.1093/ajcn/44.6.945
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between estrogen levels and diets of Caucasian American and Oriental immigrant women

Abstract: The relationship between diet and estrogens was studied in two groups of women with different dietary habits and breast cancer risks. Plasma estrogens and androgens and 24-h urinary and fecal excretion of estrogens were measured in premenopausal and postmenopausal Caucasians and recent Oriental immigrants from Southeast Asia to Hawaii. Premenopausal Caucasians had 30-75% higher plasma estrone and estradiol levels than their age-matched cohorts in Hawaii, and the postmenopausal Caucasians had 3-fold higher plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
1
2

Year Published

1988
1988
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(84 citation statements)
references
References 17 publications
4
77
1
2
Order By: Relevance
“…The decreased levels of serum E2 that we and Goldin et al (1986) have found in low-risk Asian women could well explain the further divergence of the age-specific breast cancer incidence rates in postmenopausal Japanese women compared to American white women. It is, therefore, important that the discrepancy between these results and those of Hayward et al (1978) be resolved.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The decreased levels of serum E2 that we and Goldin et al (1986) have found in low-risk Asian women could well explain the further divergence of the age-specific breast cancer incidence rates in postmenopausal Japanese women compared to American white women. It is, therefore, important that the discrepancy between these results and those of Hayward et al (1978) be resolved.…”
Section: Discussionmentioning
confidence: 62%
“…Hayward et al (1978) found no difference between the postmenopausal plasma El levels of British women (n = 30) and of Japanese women in Tokyo (n = 29), and plasma E2 levels were 11% lower in the British women. Goldin et al (1986) also found no differences in plasma El levels between American white (n = 10) and Asian women who had recently immigrated to Hawaii (n = 8); they did, however, find a three-fold increase in E2 levels in the American women.…”
Section: Discussionmentioning
confidence: 82%
“…For example, British women aged 35-44, have been found to have oestradiol concentrations 36% higher on average than those of Chinese women of the same age (Key et al, 1990). Comparisons of premenopausal Western women with Asian women living in Japan (MacMahon et al, 1974;Hayward et al, 1978;Gray et al, 1982) or China (Bernstein et al, 1990), or recent migrants to Hawaii (Goldin et al, 1986), have also, in general, found lower oestrogen levels in the group of women at lower risk of breast cancer. In post-menopausal women it has been found that American whites have oestradiol levels three times those of recent Asian migrants to Hawaii (Goldin et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of premenopausal Western women with Asian women living in Japan (MacMahon et al, 1974;Hayward et al, 1978;Gray et al, 1982) or China (Bernstein et al, 1990), or recent migrants to Hawaii (Goldin et al, 1986), have also, in general, found lower oestrogen levels in the group of women at lower risk of breast cancer. In post-menopausal women it has been found that American whites have oestradiol levels three times those of recent Asian migrants to Hawaii (Goldin et al, 1986). Similar results have been found in a comparison of rural Japanese women and white women living in southern California (Shimizu et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Elevated serum estrogen levels and increased urinary excretion rates of estrone, estradiol, and estriol have been detected in breast cancer patients compared with controls (118). Postmenopausal women living in countries with a higher risk of breast cancer, such as the United States or United Kingdom, have elevated levels of urinary and/or serum estrogens compared with women living in countries with a lower risk of breast cancer, such as Japan, China, and Singapore (120)(121)(122)(123).…”
Section: Cancermentioning
confidence: 99%